ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PADA BANK UMUM SYARIAH DI INDONESIA - Vita Tristiningtyas; Osmad Mutaher (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2013)
This study aimed to examine the effect of the Capital Adequacy Ratio ( CAR ) , Non Performing Financing ( NPF) , Net Operating Margin ( NOM ) , Financing to Deposit Ratio (FDR) , BOPO and DPK against return on Assets ( ROA ) as a proxy of the financial performance of Islamic Banks in Indonesia from 2008 to 2012 . The population in this study was 11 Islamic Banks in Indonesia . The analysis technique used in this study is a multiple linear regression. While the classical assumption used in this study include autocorrelation test , normality test, multikolonieritas , and heteroscedasticity test . The results showed that the variable CAR and DPK positive and significant impact on ROA Islamic Banks . While BOPO variable is negative and significant effect on ROA Islamic Banks . NPF variables , NOM , and FDR negative effect on ROA , but not significantly . Predictive ability of the six variables on ROA of 86.0 % , while the rest is influenced by other factors not included in the research model . The results of this study are expected to provide guidelines for the management of Islamic Banks in managing the company .